Pengaruh Kualitas Produk dan Persepsi Harga Terhadap Minat Beli Ulang Smartphone Samsung Pada Masyarakat Kota Mataram - Sasmita, Aprilia Ayu; Athar, Handry Sudiartha (ALEXANDRIA (Journal of Economics, Business, & Entrepreneurship), 2024)
This research aims to determine and analyze the Influence of Product Quality and Price Perception on Interest in Repurchasing Samsung Smartphones in the Mataram City Community. Using a sample of 80 respondents who live in Mataram, this research found that product quality has a positive and significant influence on interest in repurchasing Samsung smartphones and price perception has a positive and significant influence on intention to repurchase Samsung Smartphones. These results indicate that product quality and price perception are effective in increasing interest in repurchasing Samsung Smartphones.